MORFOFONOLOGI KATA POLIMORFEMIK BERKONSTRUKSI MORFEM TERIKAT məN- DAN MORFEM DASAR BERFONEM AWAL /k, p, s, t/ DALAM BAHASA INDONESIA: KAJIAN SECARA INDUKSI - Yani, Sofi Andri; Yusuf, Cahyo; Herpindo, Herpindo (Balai Bahasa Sumatra Barat, 2023)
This study aims to: (1) described the morphophonological process of polymorphemic words consisting of bound morphemes məN- and basic morphemes starting with phonemes /k,p,s,t/ if it is studied by induction, (2) prove the position of nasal-consonant sound segments /ŋ, m, ɲ, n/ abstracted by the nasal N when proven by the Praat program tool. Provision of data using the listening method followed by fishing, recording, and note-taking techniques. Data recording in this study using the speech analizier praat. Furthermore, the data were analyzed using the induction method (decline) and continued with the jabar-comparison technique. The results of this study presented that (a) the position of the consonant-nasal sound segment /ŋ, m, ɲ, n/ abstracted from nasal N was in the energy unit of the second syllable and was rigid at the onset of the second syllable as in the word polymorphemic [mə.ŋa.lah], polymorphemic words, for example [mə.րan.tap] was derived in bound morpheme məN- and base morpheme with initial phoneme /s/ including (s)antap. The construction of polymorphemic word sounds is compared with its derivative morphemes, phonological/morphophonological symptoms are found, among others: (1) shift of nasal consonants /ɲ/ which were initially at the onset of the syllables of the two polymorphemic words [mə.րan.tap] shifted to the coda of the first syllable in the bound morphemes of the form məր-, (2) consonant increased /s/ was the result of polymorphemic words [mə.րan.tap], and (3) changes in nasal consonants [ ɲ] coda first syllable allomorphs məր- were abstracted into N nasals so that the derived bound morpheme became məN-.